Effect of Nitrogen Fertilization Rates on Some Production and Quality Traits of Sugar Beet under Hama Governorate Conditions (Damascus University Journal of agriculture sciences, 2024)
The study was conducted at Tizin Research Station for irrigation, Hama Agricultural Research Center, General Commission for Scientific Agricultural Research (GCSAR), during summer, the growing season of 2020/2021, to study the effect of four levels of nitrogen fertilizer (0, 200, (+25%) 250 and (-25%) 150 kg. hectare-1) on some yield and quality traits of sugar beet monogerm variety (Dita). The experiment was laid according to the randomized complete block design (RCBD) with three replications. The statistical analysis exhibited that there was no significant effect on the quality traits; brix, sucrose, and purity percentages (20.92, 14.57 and 69.61%) respectively, while the nitrogen levels affected significantly the production traits and plant density, which were the highest at the addition of 250 kg. hectare-1 (102.8, 50.4, 153.3 and 3.79 ton. hectare-1 respectively). The highest value of plant number per hectare was (80.74 thousand plant. hectare-1) at a level of 250 kg. hectare-1 of nitrogen fertilization. These results assure the importance of the nitrogen fertilizer to enhance the plant's photosynthesis efficiency and dry matter accumulation.
Keywords: Sugar beet; Nitrogen fertilizer; Quality traits; Production traits